Abundance and composition of juvenile corals reveals divergent trajectories for coral assemblages across the United Arab Emirates. Issue 2 (30th January 2017) - Pratchett, Morgan S.; Baird, Andrew H.; Bauman, Andrew G.; Burt, John A.
Abstract: Marked shifts in the composition of coral assemblages are occurring at many locations, but it is unknown whether these are permanent shifts reinforced by patterns of population replenishment. This study examined the composition of juvenile coral assemblages across the United Arab Emirates (UAE). Densities of juvenile corals varied significantly among locations, but were highest where coral cover was highest. Juvenile coral assemblages within the Persian Gulf were dominated by Porites, while no Acropora were recorded. We expect therefore, continued declines in Acropora abundance, while observed dominance of Porites is likely to persist. In the Oman Sea, Pocillopora was the dominant juvenile coral, with Acropora and Stylophora also recorded. This study shows that taxonomic differences in replenishment are reinforcing temporal shifts in coral composition within the southern Persian Gulf, but not in the Oman Sea. Differences in environmental conditions and disturbance regimes likely explain the divergent responses between regions. Highlights: Juvenile coral assemblages were surveyed on UAE's Persian Gulf and Oman Sea coasts. Juveniles varied spatially and were most common where coral cover was highest. Persian Gulf juvenile communities were dominated by Porites, and Acropora were absent. Pocillopora juveniles dominated in Oman Sea; Acropora and Stylophora also occurred. Juvenile patterns likely to reinforce recent adult shifts in Persian Gulf, but not Oman Sea